Gejayan Memanggil: Social Solidarity in the Social Movement of the Digital Age - Zufar, Biko Nabih Fikri; Airlangga, Sinergy Aditya (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
Many things change in society as a result of being influenced by technology, one of which is social movements. Increasingly sophisticated technology can drive or present social movements in society. Based on these conditions, this article examines the existence of technology that can produce a social movement in society. In addition, this article uses social solidarity theory; mechanical and organic Durkheim, with a view to seeing the solidarity that appears in social movements in the digital era. This article uses a qualitative research method with a narrative research approach. The result is that social movements in the digital era only prioritize mechanical solidarity, without ensuring equal distribution of awareness of the individuals or groups involved. On the other hand, a social movement in the digital era requires organic solidarity to be able to maximize the goals of social movements.